Aplikasi Fuzzy Inference System pada Seleksi Penerimaan Santri Baru MI Kota Madiun - Budi Sasomo; Toto Nusantara; I Made Sulandra (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2025)
Admission of new students in Madrasah Ibtidaiyah (MI) is a crucial stage in maintaining the quality of students and the quality of education. Selection usually considers the Institutional Development Contribution (SPI), calistung skills, and recitation of the Quran. However, non-standardized assessment creates injustice. This research develops a Fuzzy Inference System (FIS)-based decision support system with the Mamdani model to improve the objectivity and accuracy of selection. A quantitative approach is used with the help of Microsoft Excel for modeling. The system uses inputs in the form of SPI, calistung, and mengaji, and produces outputs in the form of selection result categories. The FIS process includes problem identification, fuzzification, fuzzy rule generation, Mamdani inference, and defuzzification using the centroid method. The results show that this system is able to produce decisions that are more fair, transparent, and in accordance with the principles of Islamic education and the needs of madrasah development. The integration of fuzzy technology is proven to support more professional education governance and responsiveness to selection challenges.